Avaliação do efeito da piscicultura em sistemas aquáticos em Assis e Cândido Mota, São Paulo, por indicador de qualidade da água e análise estatítica multivariada - Simões, Fabiano dos Santos; Yabe, Maria Josefa dos Santos; Moreira, Altair Benedito [UNESP]; Bisinoti, Márcia Cristina [UNESP] (Sociedade Brasileira de Química, 2007)
In this work, the impact of fish farming activities on the Queixada, Macuco and Pari-Veado Rivers in the Paranapanema watershed was evaluated. Physical, chemical and microbiological parameters were quantified in these aquatic systems followed by application of multivariate statistical analysis (MSA) and water quality index (WQI) tools. Watersheds where fish farming activities are predominant presented WQI > 52 indicating good quality, whereas MSA demonstrated bad quality for these aquatic bodies. The results showed that the degradation in this watershed follows the fish farming activity. The MSA index is more restricted than the National Foundation Sanitation (NFS) index routinely used to infer water quality.
Assessment of fish farming effects on aquatic systems in Assis and Candido Mota, São Paulo, by using a water quality index and multivariate statistical analysis
Keywords: water quality index (WQI); multivariate statistical analysis; fish farming activities